THE INFLUENCE OF CORPORATE GOVERNANCE ON FINANCIAL PERFORMANCE: THE MEDIATING ROLE OF EARNINGS MANAGEMENT - Adi, Bayu (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to examine the impact of corporate governance mechanisms towards the financial performance of companies in Indonesia, where earnings management is applied as an intervening variable. Corporate governance is a significant element in mitigating agency conflicts that may impact a firm's financial outcomes and lead to earnings manipulation. A quantitative approach was employed, using path analysis to test the proposed relationships. 312 observations of data were collected from 78 listed industrial companies in the Indonesia Stock Exchange during 2021-2024 through purposive sampling. The results show that the percentage of independent commissioners and institutional ownership considerably reduces the earnings management behavior. However, the size of the audit committee and managerial ownership do not appear to have a major impact. Furthermore, financial performance is strongly and favorably impacted by institutional ownership and independent commissioners. However, it has been discovered that earnings management significantly and negatively affects financial outcomes. Furthermore, the evidence points to earnings management as a partial mediating factor in the relationship between corporate governance elements and financial performance. This study contributes to the body of knowledge in accounting and corporate governance by empirically evaluating the mediating function of earnings management in the link between governance systems and business financial performance in the Indonesian context.